Engaging adult learners in the learning process via accelerated learning : andragogical approach - Noor Hassline Mohamed (2012)
This study attempts to examine the effectiveness of accelerated learning with andragogical approach in engaging adult learners in the learning process. 20 learners of undergraduate psychology programmes from Open University Malaysia (OUM) are involved in the study. The approach of accelerated learning in the study incorporates the five aspects, include, create an interesting learning environment, create an emotional connection by using visuals, creatively present by using colours and sounds, activate and integrate leaners through fun activity such as interactive quiz, sms mobile learning, multisensory activities such as problem solving activities, exercises and learning games, and finally, motivate learners to engage actively in learning process. The accelerated learning is implemented in face-to-face tutorial sessions and online forums. The result of the study is useful in understanding adult learners’ interests in an open and distance learning institutions. (Abstract by author)